Rumour-spreading in social media and its Impact on Societal Security from the Perspective of University Students in United Arab Emirates Society - Al Suwaidi, Suaad Mohammed; Alomosh, Ahmad Falah (Al-Adab Journal, 2022)
The aim of this study was to identify rumour-spreading in social media and its impact on societal security from the perspective of university students in Emirati society. The descriptive analytical approach was duly used. For the purposes of this study, the questionnaire was administered as a research instrument to collate data from members of the study sample, which consisted of 313 university students in Emirati society. The study concluded that the top spreader of rumours via social media, according to the study sample, was WhatsApp. Instagram, meanwhile, was a close second, followed by TikTok. Further, the multimedia tool that contributed most to the believability of social media rumours, according to members of the sample, was videos, followed by images and lastly infographics. The results also showed that the most prevalent sorts of rumours in social media, according to the study sample, were social rumours, followed by political rumours, while security rumours came last. It was found that university students in the UAE tend to be impartial towards rumour-spreading in social media and its impact on societal security, and that the most appropriate ways to confront rumours in social media, according to the students in the sample, were through the imposition of fines and penalties on rumourmongers through social media. The results also showed that, a significance level of α≤0.05, there were no statistically significant differences attributed to gender and University type at in the students’ leanings towards rumour-spreading in social media and its impact on the societal security. Based on the results, the study recommended a tightening of controls on the various forms of social media and the taking of all deterrent measures against fake and rumour-spreading accounts.